2011
DOI: 10.1126/science.1203428
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “A Persistent Oxygen Anomaly Reveals the Fate of Spilled Methane in the Deep Gulf of Mexico”

Abstract: We hypothesized that methane from the Deepwater Horizon oil spill was quantitatively consumed and presented results from four tests supporting this finding. Subsequent published studies provide further support for our conclusions. We refute the criticisms by Joye et al., which are incorrect, internally contradictory, based on flow-rate estimates that exceed consensus values, and overall do not disprove our hypothesis or invalidate its underlying assumptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…First, the inclusion of physical dynamics corroborates a previous hypothesis (23,25) for why the extensive and persistent oxygen depletion predicted in the deep plume horizon by Joye et al (9) was not observed. Second, the physical dynamics also suggest a more complex flow field than the laminar flow used by Hazen et al (13) to estimate hydrocarbon half-lives associated with the bloom, thus calling the accuracy of the reported half-lives into question.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…First, the inclusion of physical dynamics corroborates a previous hypothesis (23,25) for why the extensive and persistent oxygen depletion predicted in the deep plume horizon by Joye et al (9) was not observed. Second, the physical dynamics also suggest a more complex flow field than the laminar flow used by Hazen et al (13) to estimate hydrocarbon half-lives associated with the bloom, thus calling the accuracy of the reported half-lives into question.…”
Section: Resultssupporting
confidence: 86%
“…Samples of these waters revealed blooms of Colwellia and a biodegradation preference for propane over ethane over methane (9,10); the model predicts concurrent blooms of OMTs mapped to Colwellia, which have been linked to consumption of ethane and propane (21). The model provides for abundant methanotroph and methylotroph production, which was observed in September and October of 2010 (2), and it independently arrives at the debated scenario (23)(24)(25) in which methanotrophs and methylotrophs constitute a significant portion of the bacterial community, even with no detectable oxygen anomaly (e.g., respiration of 0.05 μM CH 4 yields a maximum oxygen anomaly of 0.1 μM, below the detection limit; the resulting bacterial biomass, a maximum of 0.025 μmol C L −1 , would constitute up to 20% of the background community with no apparent oxygen anomaly, consistent with our previous observation) (2). Hazen et al (13) observed that, on May 30, 90-95% of the microbial community in the peak plume horizon southwest of the wellhead was Oceanospirillales; the model predicts ∼80% of the bacterial population as OMTs mapped to Oceanospirillales at this place and time (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Nitrosopumilus maritimus was reported to be dominant in the suboxic zone of the Baltic Sea (40), and the lower oxygen concentrations observed in some areas after the spill (up to 30 to 50% oxygen depletion [3]) could have favored Nitrosopumilus. Although some studies predicted this localized oxygen depletion to persist for months to years because of slow water mixing rates at depth (3,8,(17)(18)(19), the causes, extent, and duration of this depletion have been debated (20,21). Modeling efforts suggested that physical dynamics would result in the absence of an extensive and persistent oxygen depletion in the deep plume horizon (41), and recent studies of the microbial dynamics suggested that the oxygen anomaly observed at plume depth after the spill could be due to consumption of organic matter from dead organisms in the plume (23).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high degradation rates observed and slow mixing of deep water, it was suggested that oxygen depletion at plume depth might persist for several years (3,(17)(18)(19). The cause, extent, and duration of this oxygen depletion were subject to debate (8,20,21), and it is not clear how, and if, it would impact the microbial communities in the long term. Recent work also indicated that significant quantities of oil sank to the sea floor (22), potentially affecting microbial communities in the sediments.…”
mentioning
confidence: 99%
“…However, the mechanisms governing the fate of methane and other hydrocarbons into the water column are still under debate, and their probability to reach the atmosphere seems to be site-dependent [57][58][59][60][61][62][63][64]. Accordingly, although difficult, quantifying the contribution of oceanic methane to the global atmospheric budget is crucial, and this necessarily requires knowledge of local methane fluxes from submarine seeps as input.…”
Section: Introductionmentioning
confidence: 99%